Pengaruh Kelelahan antara Asistensi Pagi dan Sore terhadap Nilai Mahasiswa Pendidikan Dokter FK UNS Surakarta - Dimas Alan Setiawan; S Bambang Widjokongko; Dhoni Akbar Ghozali (Nexus Pendidikan Kedokteran dan Kesehatan, 2014)
Background: The assistance lecture program was a part of practicum activity, a part of medical educations curriculum that led to achieve Indonesians doctor competence. All this time, the assistance lecture program was held outside the regular lecture schedule, usually in the morning. Some party felt that morning assistance lecture was a burden for them. Then a policy was made to put morning assistance lecture into regular college schedule, especially at the afternoon. The other party felt that afternoon assistance was ineffective because student already had a full schedule from morning till afternoon. Student may feel tired when accepting the afternoon assistance lecture program. This research aimed to compare the effectiveness between morning assistance lecture and afternoon assistance lecture. Methods: This research was a quasi-experimental research with pretest and posttest group design study approach. This research was making an intervention to samples without samples randomization. The intervention that made is researcher performing both morning and afternoon assistance lecture program to samples. Samples of this research were medical students of Sebelas Maret University Faculty of Medicine class of 2012. Samples were taken by rule of thumb method and then samples divided by morning group and afternoon group. The number of samples was 30 persons from each group and all of them undergo pretest and posttest that contain pharmacology subject lesson. Then the result of samples pretest and posttest points compared and analyzed with unpaired T-test method. Results: Morning assistance lecture group had a mean value 0.43, bigger than afternoon assistance lecture group that only had mean value 0.40. Those were shown from the T test results with p=0.103 (p>0.05) which means there were no significant difference of pharmacology points between morning assistance lecture group and afternoon assistance lecture group. Conclusion: Based on independent T test analysis, there are no significant difference of pharmacology points between morning assistance lecture group and afternoon assistance lecture group. Keywords: Assistance, fatigue, morning, afternoon.